Morphological aspects of small-duct cholangiopathies: A minireview - Sticova, Eva; Fabian, Ondrej (World journal of hepatology, 2023)
The biliary system consists of intrahepatic and extrahepatic bile ducts lined by biliary epithelial cells (cholangiocytes). Bile ducts and cholangiocytes are affected by a variety of disorders called cholangiopathies, which differ in aetiology, pathogenesis, and morphology. Classification of cholangiopathies is complex and reflects pathogenic mechanisms (immune-mediated, genetic, drug- and toxin-induced, ischaemic, infectious, neoplastic), predominant morphological patterns of biliary injury (suppurative and non-suppurative cholangitis, cholangiopathy), and specific segments of the biliary tree affected by the disease process. While the involvement of large extrahepatic and intrahepatic bile ducts is typically visualised using radiology imaging, histopathological examination of liver tissue obtained by percutaneous liver biopsy still plays an important role in the diagnosis of cholangiopathies affecting the small intrahepatic bile ducts. To increase the diagnostic yield of a liver biopsy and determine the optimal therapeutic approach, the referring clinician is tasked with interpreting the results of histopathological examination. This requires knowledge and understanding of basic morphological patterns of hepatobiliary injury and an ability to correlate microscopic findings with results obtained by imaging and laboratory methods. This minireview describes the morphological aspects of small-duct cholangiopathies pertaining to the diagnostic process.
Keywords: Bile duct; Cholangitis; Liver biopsy; Cholangiopathy; Cholangiocytes; Histopathology